2007
DOI: 10.1021/bi0621415
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity Profiling and Identification of a New Class of Inhibitor for the Major Protease of the SARS Coronavirus,

Abstract: Severe acute respiratory syndrome (SARS) is an emerging infectious disease associated with a high rate of mortality. The SARS-associated coronavirus (SARS-CoV) has been identified as the etiological agent of the disease. Although public health procedures have been effective in combating the spread of SARS, concern remains about the possibility of a recurrence. Various approaches are being pursued for the development of efficacious therapeutics. One promising approach is to develop small molecule inhibitors of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
112
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 43 publications
3
112
1
Order By: Relevance
“…Crystallographic studies have shown that the inhibitor forms a single covalent complex with the active site cysteine residue Cys145 (Jay Davies, unpublished results). A similar irreversible peptide mimetic inactivator has been shown to form a single covalent adduct with Cys145 of 3CL pro (27). Isothermal titration calorimetry with PF-596162 was used to support the existence of a single binding site per monomer and to determine the fraction of the active sites occupied ( Figure 2C,D).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Crystallographic studies have shown that the inhibitor forms a single covalent complex with the active site cysteine residue Cys145 (Jay Davies, unpublished results). A similar irreversible peptide mimetic inactivator has been shown to form a single covalent adduct with Cys145 of 3CL pro (27). Isothermal titration calorimetry with PF-596162 was used to support the existence of a single binding site per monomer and to determine the fraction of the active sites occupied ( Figure 2C,D).…”
Section: Resultsmentioning
confidence: 99%
“…Inactivation studies with the cysteine-reactive, weakly electrophilic inactivator PF-596162 showed a 1:1 inactivation stoichiometry. Another irreversible inhibitor has been shown to specifically modify the catalytic cysteine residue of 3CL pro (27). The pH dependence of the pseudo-second-order rate constant of inactivation of 3CL pro (k obs /[IA]) with iodoacetamide is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virtual screening (Plewczynski et al, 2007;Mukherjee et al, 2008;Nguyen et al, 2011) or a high-throughput screening of small molecule libraries have identified inhibitorsincluding an anti-HIV agent and serotonin antagonist, cinanserin (Blanchard et al, 2004;Kao et al, 2004;Wu et al, 2004a;Chen et al, 2005). Other 3CL protease inhibitors identified so far belongto categories such as plant derived phenolic or flavonoid compounds (Lin et al, 2005;Nguyen et al, 2012), active site, nonactive site or competitive inhibitors (Kaeppler et al, 2005;Lee et al, 2005;Du et al, 2007;Ryu et al, 2010), ketones or ester based inhibitors (Goetz et al, 2007;Zhang et al, 2007;Ghosh et al, 2008;Shao et al, 2008;Verschueren et al, 2008;Zhang et al, 2008), modified peptidomimetic inhibitors (Ghosh et al, 2007), metal conjugated inhibitors (Lee et al, 2007;…”
Section: Viral Protease Inhibitorsmentioning
confidence: 99%
“…Similarly, most rational approaches with respect to the design of SARS-CoV M pro inhibitors mainly focus on the optimization of a scaffold privileged to covalent inhibition by the attachment of electrophilic groups. Next to the abovementioned halomethyl ketones, , -unsaturated esters acting as Michael acceptors, and aldehydes, the arsenal of appropriate reactive warheads attached to substrate-based or peptidomimetic inhibitors has been extended to phthalhydrazide moieties [122], epoxyketones [123] and aziridines [124]. Interestingly, an amide derivative (31, Fig.…”
Section: The Sars-coronavirus Main Proteinasementioning
confidence: 99%